vix aliquot Viri eam Linguam intelligent or vix aliqvot Viri ʃenes eam Lingvam intelligunt? Johannes Amos Comenius about the death of the Old Prussian language - Lemeškin, Ilja (Baltistica, 2018)
Putting the Latin source into a wider scientific circulation in 1970 V. Kiparsky, similarly to Ch. Hartknoch and J. Zubatý, relied on the collection of J. A. Comenius’ works Opera Didactica Omnia published in Amsterdam in 1657. The Czech linguist included his work Lingvarum Methodvs Novissima first published in 1648 into that collection, however, fundamental differences can be noticed between the first publication and the publication in 1657. The article discusses the reception in the early 20th century of J. A. Comenius’ testimony about the loss of the Old Prussian language.
Keywords: Old Prussian; language death; J. A. Comenius; the history of Baltic Studies; Ch. Hartknoch; J. Zubatý; O. Hujer; V. Kiparsky